Adaptation of the Start-Growth-Time Method for High-Throughput Biofilm Quantification - Thieme, Lara; Hartung, Anita; Tramm, Kristina; Graf, Julia; Spott, Riccardo; Makarewicz, Oliwia; Pletz, Mathias W. (Frontiers in Microbiology, 2021)
Colony forming unit (CFU) determination by agar plating is still regarded as the gold standard for biofilm quantification despite being time- and resource-consuming. Here, we propose an adaption of the high-throughput Start-Growth-Time (SGT) method from planktonic to biofilm analysis, which indirectly quantifies CFU/mL numbers by evaluating regrowth curves of detached biofilms. For validation, the effect of dalbavancin, rifampicin and gentamicin against mature biofilms of Staphylococcus aureus and Enterococcus faecium was measured by accessing different features of the viability status of the cell, i.e. the cultivability (conventional agar plating), growth behavior (SGT) and metabolic activity (resazurin assay). SGT correlated well with the resazurin assay for all tested antibiotics, but only for gentamicin and rifampicin with conventional agar plating. Dalbavancin treatment-derived growth curves showed a compared to untreated controls significantly slower increase with reduced cell doubling times and reduced metabolic rate, but no change in CFU numbers was observed by conventional agar plating. Here, unspecific binding of dalbavancin to the biofilm interfered with the SGT methodology since the renewed release of dalbavancin during detachment of the biofilms led to an unintended antimicrobial effect. The application of the SGT method for anti-biofilm testing is therefore not suited for antibiotics which stick to the biofilm and/or to the bacterial cell wall. Importantly, the same applies for the well-established resazurin method for anti-biofilm testing. However, for antibiotics which do not bind to the biofilm as seen for gentamicin and rifampicin, the SGT method presents a much less labor-intensive method suited for high-throughput screening of anti-biofilm compounds.